2013
DOI: 10.3747/co.20.1223
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness of Systemic Therapies for Metastatic Pancreatic Cancer

Abstract: ConclusionsThe most cost-effective treatment for metastatic pancreatic cancer depends on the societal wtp threshold. If the societal wtp threshold were to be relatively high or if drug costs were to be substantially reduced, folfirinox might be cost-effective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(23 citation statements)
references
References 18 publications
(28 reference statements)
2
20
0
Order By: Relevance
“… 10 The cost is approximately 25,625 USD for one month of gemcitabine/capecitabine treatment. 15 This study showed that adjuvant therapy does not confer an overall survival benefit for patients with resected, stage IA, sub-centimeter T1a/T1b PDAC. Thus, the repercussions of therapy cost and side effects of treatment may outweigh the benefits in this group of PDAC patients.…”
Section: Discussionmentioning
confidence: 73%
“… 10 The cost is approximately 25,625 USD for one month of gemcitabine/capecitabine treatment. 15 This study showed that adjuvant therapy does not confer an overall survival benefit for patients with resected, stage IA, sub-centimeter T1a/T1b PDAC. Thus, the repercussions of therapy cost and side effects of treatment may outweigh the benefits in this group of PDAC patients.…”
Section: Discussionmentioning
confidence: 73%
“…The authors demonstrated that FOLFIRINOX had an 80 % probability of being cost-effective at the $100,000/QALY threshold. Another Canadian study comparing gemcitabine/erlotinib with gemcitabine had 0 % probability of being cost-effective at the same willingness to pay threshold [20]. Due to the differences in costs and healthcare systems between countries, conclusions drawn from one country cannot easily be applied to another country [21].…”
Section: Discussionmentioning
confidence: 98%
“…Peripheral sensory neuropathy À0.226 Assumed equal to peripheral neuropathy Peripheral neuropathy À0.226 [39] Dehydration 0.000 Assumed no reduction Asthenia À0.204 [37] Abdominal pain À0.069 [40] Nausea À0.048 [36] Diarrhea À0.261 [37] Vomiting À0.103 [41] Loss of appetite 0.000 Assumed no reduction Pulmonary embolism À0.195 [42] Pneumonia À0.440 [43] Febrile neutropenia À0.150 [41] Cholangitis À0.440 Assumed equal to event with greatest impact on quality of life Hyperbilirubinemia À0.204 Assumed equal to fatigue Nab-paclitaxel in metastatic pancreatic cancer…”
Section: Parameter Utility Sourcementioning
confidence: 99%